2006
DOI: 10.1177/159101990601200212
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Recurrent Internal Carotid Artery Pseudoaneurysm with the Wallgraft Endoprosthesis

Abstract: The use of covered stents to treat traumatic carotid artery pseudoaneurysms is increasingly being documented. Adjunctive antiplatelet therapy is mandatory. We present a case of bilateral traumatic carotid artery pseudoaneuryms in which antiplatelet therapy was contraindicated at presentation, thereby dictating alternative treatment with coil embolization alone. Subsequent aneurysmal recurrence was successfully treated with the Wallgraft prosthesis. The literature on the use of the Wallgraft prosthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The literature provides one instance where a patient had recurrent left ICA pseudoaneurysm after coil embolization, which was performed 4 years prior to presentation. [ 24 ] Our patient exhibited recurrence 15 years after ICA occlusion. Endovascular therapy was no longer an appropriate option.…”
Section: Discussionmentioning
confidence: 84%
“…The literature provides one instance where a patient had recurrent left ICA pseudoaneurysm after coil embolization, which was performed 4 years prior to presentation. [ 24 ] Our patient exhibited recurrence 15 years after ICA occlusion. Endovascular therapy was no longer an appropriate option.…”
Section: Discussionmentioning
confidence: 84%
“…However, there are opposite reports showing that ICA pseudoaneurysms may continue to opacify and enlarge after the procedure and suggesting that there is always a potential for pseudoaneurysm recanalization with bare stent implantation, even if it was combined with coil embolization [ 1 ]. Sibtain et al reported on a case of bilateral traumatic carotid artery pseudoaneurysms which were first treated by using coil embolization instead of covered stent grafts because of contraindicated antiplatelet theraphy at presentation [ 8 ]. But because of the recurrence of ICA pseudoaneurysm 3 months after coil embolization, definite treatment with Wallgraft endoprosthesis was introduced.…”
Section: Discussionmentioning
confidence: 99%